Transformational Leadership Mentoring to Form the Religious and Disciplinary Character of Elementary School Principals in Central Lombok - Sumiadi, Raden; Syahrir, Syahrir; Sarwadi, Gita; Yasa, I Putu Buda; Uli, Aprilla Sinta; Junadi, Junadi (Abdi Masyarakat, 2025)
Transformational leadership is a style focused on change and the development of positive values within educational institutions. The principal, as a leader in learning, has the duty to direct all members of the school towards developing a robust religious and disciplined character. Nonetheless, observations conducted in various elementary schools in Central Lombok Regency reveal that the application of transformational leadership values remains limited, particularly concerning the principals' roles as religious role models and their discipline. This community service initiative seeks to offer transformational leadership support to elementary school principals in Central Lombok to cultivate a religious and disciplined character in school administration. The activity method is executed in four stages: (1) preparation and collaboration with the local education office, (2) training and workshops in transformational leadership, (3) direct support at schools, and (4) assessment and reflection on the outcomes of the activity. This initiative engaged 35 elementary school principals from Praya District, Central Lombok over a period of three day. The activity's outcomes demonstrated a notable improvement in the principals' comprehension of transformational leadership, their capacity to create a vision and mission rooted in religious values, and their consistency in enforcing work discipline within the school setting. Moreover, a network of key communities was established aimed at enhancing religious culture and discipline within their individual schools. This mentoring initiative showcased the success of a transformational leadership style as a character-development strategy for elementary school principals in Central Lombok. There are hopes that comparable initiatives can persistently evolve in a sustainable manner to enhance the quality of leadership and educational administration at the primary school level.